2007
DOI: 10.1093/intqhc/mzm061
|View full text |Cite
|
Sign up to set email alerts
|

Comparing patient reports about hospital care across a Canadian-US border

Abstract: The difference observed on the 'continuity and transition' indicator might be the only one somewhat meaningful, and might be explained by health maintenance organization reimbursements' mechanisms and hospital quality improvement initiatives available in western New York, as well as by the fact that occupancy rates in western New York border the 60% compared with the 95% in southern Ontario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…These data also suggest that comparisons of patient satisfaction scores across jurisdictional boundaries should be approached carefully and that more focused comparisons between clinical groupings of patients hospitalized in similar settings may be more appropriate ways of generating crossjurisdictional comparisons of performance [24]. Alternatively, comparisons of adjusted scores across time within a jurisdiction may be a safer approach to comparative performance reporting of patient perceptions of care, that is comparing the amount of improvement, and one that is more compatible with improvement-oriented theoretical models like patient-centered care [25].…”
Section: Discussionmentioning
confidence: 97%
“…These data also suggest that comparisons of patient satisfaction scores across jurisdictional boundaries should be approached carefully and that more focused comparisons between clinical groupings of patients hospitalized in similar settings may be more appropriate ways of generating crossjurisdictional comparisons of performance [24]. Alternatively, comparisons of adjusted scores across time within a jurisdiction may be a safer approach to comparative performance reporting of patient perceptions of care, that is comparing the amount of improvement, and one that is more compatible with improvement-oriented theoretical models like patient-centered care [25].…”
Section: Discussionmentioning
confidence: 97%
“…Lasek, Barkley, Harper, and Rosenthal (1997) found that patients who completed hospital opinion surveys were more likely than non-respondents to be female, older, married, and report their health status as better. These demographic characteristics also influence patients’ evaluation of their care (Brown et al, 2008; Hargraves et al, 2001; Kravitz, 2001); patients who complete hospital surveys are also more likely to have positive perceptions of their hospital experience (Mazor, Clauser, Field, Yood, & Gurwitz, 2002; Perneger, Chamot, & Bovier, 2005). Consequently, the patients who participated in our study may not be representative of all patients admitted to the same unit.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that these symptoms (pain, in particular) are poorly controlled during hospitalization (Kris & Dodd; Toscani, Di Giulio, Brunelli, Miccinesi, & Laquintana, 2005). Other researchers have found modest but statistically significant differences in symptom management across both hospitals and nursing units, unexplained by patient characteristics (Brown, Sandoval, Murray, & Boissonnault, 2008; Desbiens et al, 1996). These findings suggest that organizational characteristics may influence the extent to which patient symptoms are perceived as effectively managed during hospitalization.…”
mentioning
confidence: 93%
“…The sampled patients allowed to estimate the population parameters for each FAG with a confidence level of 95% and a confidence interval of 10%. The survey, conducted by the Management and Health Laboratory of the Sant’Anna School of Advanced Studies of Pisa, was administered by the Computer Assisted Telephone Interview technique, which was preferred to other data collection techniques because it obtains results quickly and reaches low literacy groups [57]. Due to the aims of our study, in the analysis we considered only FAGs with at least one GP working within a PCC.…”
Section: Methodsmentioning
confidence: 99%
“…This was measured as the overall care evaluation, through a 5-point Likert scale. This variable is usually used to evaluate the GP performance within the Tuscany Region healthcare system [50], after being transformed into a 0–100 scale with higher scores indicating better evaluations [5759]. Specifically ratings of 1, poor; 2, fair; 3, good; 4, very good and 5, excellent were converted to the scores of 0, 25, 50, 75 and 100, respectively, in order to identify more clearly the variability among health services evaluated [57].…”
Section: Methodsmentioning
confidence: 99%